Analysis of job satisfaction of the nursing staff of a primary health care unit - Ione Carvalho Pinto; Carla Santa Maria Marciliano Panobianco; Fabiana Costa Machado Zacharias; Alexandre Fávero Bulgarelli; Tânia Silva Gomes Carneiro; Mariana Figueiredo Souza Gomide; Ricardo Alexandre Arcêncio
This was a cross-sectional, observational study conducted in an outpatient specialty district health unit in the city of Ribeirão Preto, in the southeastern Brazilian state of São Paulo, with the aim to analyze the job satisfaction of the nursing staff. Data were collected using the Index of Work Satisfaction (IWS), a validated instrument which was applied to 23 members of the nursing team in January 2012. Among the components of job satisfaction, participants considered Interaction to be most important, followed by Professional Status, Job Requirements, Organizational Policies, Remuneration and Autonomy. The combined mean Index of Work Satisfaction obtained was 8.29, corresponding to poor job satisfaction among the studied population, as most of the studies in the literature that used the same instrument had scores between 12 and 37.